Gamification artifacts and crowdsourcing participation: Examining the mediating role of intrinsic motivations. (April 2018) - Feng, Yuanyue; Jonathan Ye, Hua; Yu, Ying; Yang, Congcong; Cui, Tingru
Abstract: Participation of individual workers (i.e., solvers) is critical to the viability and success of crowdsourcing platforms. Past literature indicates that gamification artifacts, by intriguing solvers' intrinsic motivations, can encourage solvers' participation in crowdsourcing. Nevertheless, little research has systemically theorized how intrinsic motivations mediate the relationship between gamification artifacts and crowdsourcing participation. Based on the motivational affordance perspective and related literature, this study theorizes gamification artifacts i.e., point rewarding and feedback giving, and identifies four intrinsic motivations (i.e., self-presentation, self-efficacy, social bonds, and playfulness) in the context of crowdsourcing. It then hypothesizes the mediating effects of the four intrinsic motivations on the relationships between the two gamification artifacts and crowdsourcing participation. It tests the model using survey data from 295 solvers in a large crowdsourcing platform. Results show that self-presentation, self-efficacy and playfulness positively mediates the impacts of two gamification artifacts on solvers' participation. Theoretical contributions and practical implications are discussed. Highlights: Conceptualize two gamification artefacts: point rewarding and feedback giving. Identify four types of intrinsic motivations. Theorize and empirically validate the mediating effects of intrinsic motivations. Integrate motivational affordance perspective with the gamification literature.